Characteristics of Extreme Poverty in the Province of Bangka Belitung Islands - Zikri Rahmani; Devi Valeriani; Ayu Wulandari; Muhammad Faisal Akbar; Agung Rizki Putra; Misbahul Munir; Rozi Rozi (Equity: Jurnal Ekonomi, 2024)
This study aims to analyze the characteristics of poverty in seven districts and cities in the Bangka Belitung Islands Province. This study uses primary and secondary data from the Central Bureau of Statistics (BPS) and other relevant sources. The analysis was conducted descriptively to identify factors that influence poverty, such as the age of the poor, marriage, education level, number of dependents, type of employment, income, living conditions, government assistance and health. The results show that poverty in Bangka Belitung is more dominant in rural areas than urban areas. Low education levels and limited access to health services are the main causes of poverty in this area. In addition, the community's dependence on the fluctuating mining sector also affects the economic stability of households. This study also found significant income inequality between low- and highincome groups. Based on these findings, efforts to improve access to education and health, as well as economic sector diversification to reduce unemployment are recommended. More inclusive policies are needed to sustainably address poverty in the region.